2014
DOI: 10.1007/s11357-014-9626-3
|View full text |Cite
|
Sign up to set email alerts
|

p62/SQSTM1 at the interface of aging, autophagy, and disease

Abstract: Advanced age is characterized by increased incidence of many chronic, noninfectious diseases that impair the quality of living of the elderly and pose a major burden on the healthcare systems of developed countries. These diseases are characterized by impaired or altered function at the tissue and cellular level, which is a hallmark of the aging process. Age-related impairments are likely due to loss of homeostasis at the cellular level, which leads to the accumulation of dysfunctional organelles and damaged m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
88
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 150 publications
(225 reference statements)
2
88
0
4
Order By: Relevance
“…In addition, several studies have identified changes with age in signaling pathways (i.e. mTOR, SIRT, FOXO) that could contribute to reduced induction of autophagy and autophagosome formation (Bitto et al., 2014; Park et al., 2016; Perluigi, Di Domenico & Butterfield, 2015; Schiavi & Ventura, 2014). Future analysis will be required to explore the molecular requirements that determine the recruitment of motor proteins to AVs and LYS and the potential impact in this process of age‐associated changes in these signaling routes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have identified changes with age in signaling pathways (i.e. mTOR, SIRT, FOXO) that could contribute to reduced induction of autophagy and autophagosome formation (Bitto et al., 2014; Park et al., 2016; Perluigi, Di Domenico & Butterfield, 2015; Schiavi & Ventura, 2014). Future analysis will be required to explore the molecular requirements that determine the recruitment of motor proteins to AVs and LYS and the potential impact in this process of age‐associated changes in these signaling routes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to MeHg-induced inhibition of p62 by lysosomal disruption (Daré et al, 2001; Tofighi et al 2011). p62 has multiple domains to regulate cellular events (Bitto et al, 2014; Wang et al 2014), and may trigger nuclear factor-κB (NF-κB) activity to promote cell survival responses (Chen et al 2014). Thus, the significance of enhanced p62 protein by MeHg needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…As p62 appears to play an important role in maintaining mitochondrial quality control through mitophagy, it is possible that the loss of p62 in pancreatic β cells may cause mitochondrial dysfunction and thus result in impaired glucose tolerance [5]. Normal β-cell function and mass in β-cell-specific p62-deficient mice suggested redundant autophagy receptors; for instance, NBR1, which shares similar functional domains with p62, may have a compensatory role in mitophagy when p62 is deficient [26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elucidating the molecular mechanisms underlying pancreatic β-cell dysfunction is a key to understanding the pathology of diabetes [3,4]. Sequestosome 1 (SQSTM1, referred to hereafter as p62) is a multifunctional scaffold protein that can interact with several signaling pathways through its functional subdomains, including the Phox and Bem1 (PB1) domain, zinc-finger domain, TNF receptor-associated factor 6 (TRAF6)-binding domain, and Kelch-like ECHassociated protein 1 (Keap1) interacting region (KIR) [5][6][7]. p62/SQSTM1 can activate the antioxidant response by interacting with the Keap1-Nrf2 pathway [8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation